Portuguese spelling in primary grades: complexity, length and lexicality effects - Mesquita, Ana (2021)
This study investigates spelling abilities of 189 second, third, and fourth graders using a word and pseudoword dictation task in European Portuguese. We analyzed the effect of orthographic complexity on spelling accuracy and the moderating role of length (two vs. three syllables), lexicality (words vs. pseudowords), and grade (second, third, and fourth). Each item represented one of the following orthographic complexity categories: digraph, contextual consistency, position consistency, consonant cluster, stress mark, inconsistency, and silent letter ‹h›. Digraphs and position consistencies reached high levels of accuracy already in Grade 2, but stress marks, inconsistencies, and the silent letter ‹h› were not yet fully mastered by the end of primary school. Performance across complexities was more discrepant in Grade 2 than in Grades 3 and 4. Moreover, within each complexity, there were larger differences between Grades 2 and 3 than between Grades 3 and 4. Words were better spelled than pseudowords in position consistency and stress mark categories, and a shorter length improved accuracy only in consonant clusters and stress marks. These findings underline the importance of applying learning and teaching strategies in early education adapted to the properties of the writing system to be learned.